2012
DOI: 10.1111/j.1600-079x.2012.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduces lung oxidative stress in patients with chronic obstructive pulmonary disease: a randomized, double‐blind, placebo‐controlled study

Abstract: Chronic obstructive pulmonary disease (COPD), a major cause of death and disability, is attributed to an abnormal inflammatory response by the lungs to noxious substances, primarily from cigarette smoke. Although oxidative stress is regarded as central to the pathogenesis of COPD, very few studies have examined the effects of antioxidants in this condition. This was a randomized, double-blind, placebo-controlled study on the effects of melatonin in COPD. Thirty-six consecutive patients with clinically stable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 55 publications
2
45
0
2
Order By: Relevance
“…The remaining 278 references could be utilized to establish the increase in 8-iso-PGF 2α levels associated with medical conditions [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [103], [104], [105], [106], [107], [108], [109], [110], [111], [112], [113], [114], [115], [116], [117], [118], [119], [120], [121], [122], [123], [124], [125], [126], [127], [128], [129], [130], [131], [132], [133], [134], [135], [136], [137], [138], [139], [140], [141], [142], [143], [144], [145], [146]…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 278 references could be utilized to establish the increase in 8-iso-PGF 2α levels associated with medical conditions [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [103], [104], [105], [106], [107], [108], [109], [110], [111], [112], [113], [114], [115], [116], [117], [118], [119], [120], [121], [122], [123], [124], [125], [126], [127], [128], [129], [130], [131], [132], [133], [134], [135], [136], [137], [138], [139], [140], [141], [142], [143], [144], [145], [146]…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a 2-month melatonin supplementation caused a reduction in TBARS concentration and a rise in SOD activity in the metabolic syndrome patients [38]. In other studies, melatonin supplementation improved the proantioxidant state in patients suffering from diseases linked to obesity, including diabetes mellitus [65], hypertension [66], and chronic obstructive pulmonary disease [67]. The direct and indirect antioxidant properties of melatonin and its metabolites are well documented [18, 21, 23].…”
Section: Discussionmentioning
confidence: 99%
“…In a study in COPD patients, melatonin was shown to reduce markers of oxidative stress, with improvements in dyspnoea, without any significant changes in lung function [261].…”
Section: Potential Treatment For Ageingmentioning
confidence: 98%